2019
DOI: 10.1159/000502421
|View full text |Cite
|
Sign up to set email alerts
|

High Maternal and Low Cord Blood Leptin Are Associated with BMI-SDS Gain in the First Year of Life

Abstract: <b><i>Background:</i></b> Early infant weight development influences metabolic regulation later in life. For the prevention of obesity and metabolic diseases, it is important to understand the underlying mechanisms in detail. <b><i>Objectives:</i></b> This study aims to examine the effects of maternal anthropometric, sociodemographic, and lifestyle factors on maternal and cord blood leptin levels at birth and on the development of body mass index (BMI) standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…We demonstrated that higher maternal and lower cord-blood leptin levels are associated with a higher BMI SDS increase during the first year of life. Maternal leptin is influenced by maternal BMI and weight gain during pregnancy, and cord-blood leptin is influenced by maternal physical activity [111]. These results are in line with findings by Simpson et al [115], who found that higher cord-blood leptin was associated with higher z-scores of fat mass, waist circumference, and BMI at nine years of age, although they did not take lifestyle factors such as physical activity into account.…”
Section: Early-life Programming and The Influence Of Different Adipoksupporting
confidence: 88%
See 2 more Smart Citations
“…We demonstrated that higher maternal and lower cord-blood leptin levels are associated with a higher BMI SDS increase during the first year of life. Maternal leptin is influenced by maternal BMI and weight gain during pregnancy, and cord-blood leptin is influenced by maternal physical activity [111]. These results are in line with findings by Simpson et al [115], who found that higher cord-blood leptin was associated with higher z-scores of fat mass, waist circumference, and BMI at nine years of age, although they did not take lifestyle factors such as physical activity into account.…”
Section: Early-life Programming and The Influence Of Different Adipoksupporting
confidence: 88%
“…According to Vicker et al [110], leptin is posited to exert programming effects on central and peripheral energy-regulating pathways during a critical period of fetal and infant development. Accordingly, several researchers [111,112] investigated leptin as a candidate prognostic biomarker for obesity risk in later life. It was documented that umbilical cord blood leptin levels are positively correlated with neonatal body weight and fat mass [113].…”
Section: Early-life Programming and The Influence Of Different Adipokmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional, prospective study was performed between December 2013 and April 2014 in the obstetric unit of a tertiary referral center. The study was part of a larger study, parts of which have been published [28] , [29] , [30] . Study design and consent forms were approved by the institutional ethics committee (number 269/13).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these profiles are suggested to be associated with developmental programing in later life [ 41 , 42 ]. Because the degree of cord leptin is positively correlated with maternal leptin levels [ 18 , 23 , 36 , 43 ], and representative of fetal growth and newborn weight, adiposity, and BMI during pregnancy [ 17 , 18 , 23 , 26 , 36 , 43 , 44 , 45 , 46 ], the levels of cord leptin (approximately 15 ± 16 ng/mL; [ 23 ]) are considered to be a key predictor of childhood cardiovascular and metabolic state. Cord leptin levels can be linked with birth weight of neonates from women with gestational obesity and/or diabetes mellitus as well [ 36 , 47 , 48 ].…”
Section: Early Leptin For Future Cardiometabolic Outputmentioning
confidence: 99%